Indian Parents' Perspective towards Brand Loyalty and Kids’ Wear Safety - Kothari, Vasant; Mathews, Soney (2015)
Parental care is an essential part of human nature. Parents have the most important role for ensuring the safety and wellbeing of their children. Children of all ages are at risk of injury from wearing defective clothing. Product safety refers to the reduction in the probability that use of a product will result in injury, death or negative consequences to the people who are going to use it. Customer satisfaction and brand loyalty is an evolving trend that is considered an essential concern for which the business firms are very sensitive. Study has been conducted to know whether Indian parents will be loyal to the brands who will provide safe garments for the kids. In this study, the data has been collected with the help of structured questionnaire from 1235 parents from Bengaluru, India. The respondents were selected through stratified random sampling. This study proved that kidswear safety and customer loyalty have strong effect. Irrespective of gender, education, profession and family income, parents are ready to loyal with the brand which is going to provide safe garments for their kids.